THE DEPENDENCE OF THE CHOICE OF THE ALLOPLASTY COMPLEX ABDOMINAL WALL DEFECTS EXPRESSION OF MORPHOLOGICAL CHANGES OF TISSUES AND RISK OF INCREASED INTRA-ABDOMINAL PRESSURE - Лисенко, Р.Б. (World of Medicine and Biology, 2016)
Results of surgical treatment of 360 patients with complex abdominal wall defects, which carried alloplasty for the period 2005-2015. Choose how alloplasty was individual and was in direct proportion to the size of the defect, morphological changes in the tissues of the abdominal wall, the degree of deficiency of diastase direct abdominal muscles, the possibility of construction without much tension, the risk of increased intra-abdominal pressure, the likelihood of other postoperative complications. Proved that consideration for patients with complex abdominal wall defects degree diastase recti mascles, the degree of tissue deficiency of the anterior abdominal wall, abdominal pressure, which is defined in terms of modeling of the abdomen, as after alloplasty allows more objectively, differentiated determine the optimal method of surgery.